Draft Annual Plan 1980-81 Vol. II Uttar Pradesh - Planning Commission (Planning Commission, 1979)
The Annual Plan of 1980-81 for Agricultural Production is being drawn up under the shadow of one of the most serious droughts in many decades. Failure of monsoons and attendant power and diesel shortages on an unprecedented scale have brought the entire agrarian scene in total disarray. The adverse impact of the drought is evident from the fact that against an all time high foodgrain production of 228 lakh tonnes in 1978-79, the anticipated production during 1979- 80 would be only around 160 lakh tonnes.
Uttar Pradesh Planning Department